Islamic Branding Experience dan Customer Citizenship Behaviour terhadap Keputusan Menggunakan Layanan LinkAja Syariah - Safira, Raja Ela; Rahmanto, Dhidhin Noer Ady (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
The influence of Islamic branding experience and customer citizenship behavior on the decision to use sharia linkaja services is the focus of this research, this is due to the increasing use of digitalization of sharia finance. The sample used was 252 respondents, the sampling technique used purposive sampling, namely the selection of samples with specified criteria. The results show that partially Islamic branding experience has a significant effect on decisions to use services, then customer citizenship behavior has a positive and significant effect on decisions to use services, which means that the better customer citizenship behavior, the more decisions to use services. Simultaneously, both Islamic branding experience and customer citizenship behavior have a positive and significant effect on decisions to use services simultaneously.Islamic branding experience dan customer citizenship behaviour terhadap keputusan menggunakan layanan linkaja syariah menjadi fokus penelitian dikarenakan meningkatnya penggunaan digitalisasi keuangan syariah. Sample yang diperoleh 252 responden, teknik pengambilan sample menggunakan purposive sampling, yaitu pemilihan sample dengan kriteria tertentu. Hasil penelitian menunjukkan secara parsial islamic branding experience berpengaruh signifikan terhadap keputusan menggunakan layanan, Selanjutnya customer citizenship behaviour berpengaruh positif dan signifikan terhadap keputusan menggunakan layanan artinya semakin baik customer citizenship behaviour maka semakin meningkatkan keputusan menggunakan layanan. Secara simultan baik islamic branding experience dan customer citizenship behaviour berpengaruh secara bersamaan positif dan signifikan terhadap keputusan menggunakan layanan.